Credit-Module System is an Advanced Experience of Modern Education - Madaminov Furqatjon Shuhratjon O’g’li (Zien Journals, 2022)
In this article, the Cabinet of Ministers of the Republic of Uzbekistan dated 31.12.2020. 824, based on this decision, the regulation on the procedure for introducing the credit-module system into the educational process in higher education institutions and the main concepts in it, the orientation of the credit- module system to independent education and educational provides information about the important features and advantages of the process.
Keywords: credit module; curriculum; education; trajectory